The edge Wiener type of topological indices - Soltani, Abolghasem; Iranmanesh, Ali; Majid Z.A. (Utilitas Mathematica, 2013)
In this paper,we introduce a new topological index,called the edge Wiener type index. We give an explicit formula of some edge Wiener type indices,particular the edge Wiener index,for join of two graphs.